Between Power and Principle: A Study of Legal Legitimacy under International Law in the Iran–Israel–U.S. Trilateral Conflict - Khoirunnisa, Khoirunnisa; Jubaidi, Didi (GLOBAL INSIGHT JOURNAL, 2025)
The trilateral conflict involving Iran, Israel, and the United States represents one of the most persistent and complex geopolitical tensions in the Middle East. Rooted in ideological opposition, strategic competition, and concerns over nuclear proliferation, this conflict has had far-reaching implications for regional stability and the credibility of international legal norms. Each actor, Iran, Israel, and the United States has engaged in actions that reflect differing perceptions of threat and power projection, often justified through contested interpretations of self-defense and sovereignty. This study raises a central question: to what extent do the actions of Iran, Israel, and the United States in their ongoing conflict reflect compliance with or violations of the core principles of international law, particularly those relating to state sovereignty, non-intervention, and the lawful use of force? The objective of this research is to analyze how the legal justifications and strategic behaviors of the three actors align with or undermine international legal norms. Employing a qualitative, descriptive-analytical method, the study draws on official documents, United Nations reports, and scholarly literature to assess relevant events, such as targeted killings, cross-border airstrikes, and proxy warfare. The findings suggest that all three states have frequently invoked self-defense in ways that stretch or sidestep legal boundaries, contributing to a pattern of norm erosion and legal ambiguity. In conclusion, this conflict illustrates a broader legitimacy crisis in international law and underscores the need for stronger, more consistent multilateral mechanisms to uphold legal accountability in global security affairs.